Increasing the Strength Properties in Weak Soil Using Microbial Techniques - Suriya, Pa.; Sangeetha, S.P. (Journal of Environmental Accounting and Management, 2026)
In Microbial-Induced Calcite Precipitation (MICP) has been introduced in the field of ground improvement. The applications of this method shows potential in several fields like improvement of strength and durability of concrete, bricks, sand permeability, soil strength etc., and various works are being conducted on these fields in the current scenario. To promote the engineering properties of the material after MICP treatment, need to have study the relevant crystal mineralization process and analyses the influences on the soil engineering properties. The main aim of this paper is to analyses the behavior of various bio geo chemical processes between the soil mineralogy, solid soil grains, water or fluid, and gases in the voids, beneath the soil surface after employing microbes as strengthening consultant. Geotechnical applications currently being inquired which includes the process of cementation of sands, to enhance bearing capacity and liquefaction resistance, Carbon sequestration, erosion control of soil, controlling the groundwater flow, and remediation of soil and groundwater impacted by metals and radio-nuclides.